CuGaO2: A Promising Inorganic Hole‐Transporting Material for Highly Efficient and Stable Perovskite Solar Cells - Zhang, Hua; Wang, Huan; Chen, Wei; Jen, Alex K.‐Y. (Advanced materials (Weinheim), 2017)
The p‐type inorganic semiconductor CuGaO2 as a hole‐transporting layer (HTL) in perovskite solar cells (PSCs) provides higher carrier mobility, better‐energy level matching, and superior stability, as well as low‐temperature processing technique. Compared to organic HTL, a very competitive PCE of 18.51% with long‐term stability is achieved. This indicates that CuGaO2 is a promising HTL for efficient and stable PSCs.